Influence of surface chemistry and point defects in TiN based electrodes on electrochemical capacitive storage activity. (August 2018) - Achour, Amine; Islam, Mohammad; Ahmad, Iftikhar; Le Brizoual, Laurent; Djouadi, Abdou; Brousse, Thierry
Abstract: The effect of surface chemistry of reactive sputtered TiN electrodes in the electrochemical capacitors (ECs) was investigated. The TiN films were produced on vertically aligned carbon nanotubes. X-ray photoelectron spectroscopy analysis revealed surface defects generation with no effect on morphology. Cyclic voltammetry experiments were performed in aqueous 0.5 M K2 SO4 solution and 1 M Et4NBF4 ((tetraethylammonium tetrafluoroborate)) organic electrolyte. The presence of oxygen vacancies and Ti interstitials on the top surface layer lead to enhanced electrochemical capacitive charge storage. Such findings open the way to design nitride films with optimized surface chemistry for use in the ECs. Graphical abstract: Unlabelled Image